High serum cytokine levels may predict the responsiveness of patients with severe asthma to benralizumab. (3rd August 2022) - Watanabe, Shizuka; Suzukawa, Maho; Tashimo, Hiroyuki; Ohshima, Nobuharu; Asari, Isao; Imoto, Sahoko; Kobayashi, Nobuyuki; Tohma, Shigeto; Nagase, Takahide; Ohta, Ken
Abstract: Objective: Benralizumab, a humanized monoclonal antibody against human IL-5 receptor alpha, is effective in treating eosinophilic severe asthma. However, patients' response to benralizumab varies widely. In this study, we aimed to identify a new serum biomarker to accurately predict benralizumab response. Methods: Seventeen benralizumab-treated patients with severe eosinophilic asthma were enrolled. Blood samples were collected; pulmonary function tests were performed and questionnaires were disseminated at baseline and after 1, 2, 4, and 6 months of treatment. Blood cytokine levels were measured. Response was defined as an elevation in forced expiratory volume in 1 s of at least 10.4% from baseline after 4 months of treatment. Results: There were nine respondents and eight non-respondents. The non-responders showed significantly higher baseline serum interferon-γ; interleukin (IL)-4, -5, -6, -7, and -12p70; IL-17/IL-17A; IL-17E/IL-25; IL-18/IL-1F4; chemokine (C-C motif) ligand (CCL)3/macrophage inflammatory protein (MIP)-1α; CCL4/MIP-1β; CCL11/eotaxin; matrix metalloproteinase-12; tumor necrosis factor-α, and thymic stromal lymphopoietin levels. After benralizumab administration, the serum CCL3/MIP-1α and CCL11/eotaxin levels significantly and persistently increased in the responders (CCL3/MIP-1α, responders: 144.5 ± 37.9 pg/ml (baseline) vs. 210.3 ± 59.4 pg/ml (4 months), p  = 0.009; non-responders: 270.8 ± 139.8 pg/ml (baseline) vs. 299.5 ± 159.9 pg/ml (4 months), p  = 0.33; CCL11/eotaxin, responders: 167.9 ± 62.6 pg/ml (baseline) vs. 326.7 ± 134.4 pg/ml (4 months), p  = 0.038; non-responders: 420.9 ± 323.1 pg/ml (baseline) vs. 502.1 ± 406.0 pg/ml (4 months), p  = 0.30). Conclusion: Low baseline serum inflammatory cytokine levels may be useful in predicting a good benralizumab response. Supplemental data for this article is available online at at www.tandfonline.com/ijas .